Evaluating response to mood stabilizers in patients with mixed depression: a study of agreement between three different mania rating scales and a depression rating scale - Shansis, Flávio Milman; Reche, Mateus; Capp, Edison (Journal of affective disorders, 2016)
Background - The aim of the present study was to evaluate agreement between three pairs formed by one of three mania scales (Young Mania Rating Scale [YMRS], Bech-Rafaelsen Mania Scale [BRMS], or the Clinician-Administered Rating Scale for Mania [CARS-M]) and a single depression scale (21-item Hamilton Depression Rating Scale [21-HAM-D]) for evaluation of response to mood stabilizers in patients with mixed bipolar disorder. - Methods - Between 2010 and 2014, 68 consecutive bipolar type I and II outpatients with mixed depression as per DSM-IV-TR and Cincinnati criteria were included in this 8-week open-label trial to randomly receive carbamazepine, lithium carbonate, or valproic acid as monotherapy. - Results - Patterns of response (defined as a reduction of at least 50% in one of the mania scales and on the 21-HAM-D) were strikingly similar: 21-HAM-D+YMRS=22.1%, 21-HAM-D+BRMS=20.6%, and 21-HAM-D+CARS-M=23.5% (p<0.368). Assessment of agreement revealed very high kappa coefficients: 21-HAM-D+YMRS vs. 21-HAM-D+CARS-M, kappa=0.87; 21-HAM-D+YMRS vs. 21-HAM-D+BRMS, kappa=0.78; 21-HAM-D+CARS-M vs. 21-HAM-D+BRMS, kappa=0.91 (p<0.001). - Limitations - The decision to combine a depression rating scale with any one mania rating scale to assess treatment response in patients with mixed depression is questionable. - Conclusions - The present study suggests that any one of the three tested mania rating scales (YMRS, BRMS, and CARS-M) can be combined with the 21-HAM-D to assess treatment response in patients with mixed bipolar disorder. This should give clinicians an added measure of confidence in using this strategy until valid, and specific instruments are developed for assessment of mixed states.
Gesehen am 05.05.2020